1
0
Fork 0

Added several of sections in set theory.

This commit is contained in:
Luc Bijl 2023-12-30 20:51:25 +01:00
parent b8692bc71f
commit e631fe7a0f
4 changed files with 69 additions and 0 deletions

View file

@ -71,6 +71,10 @@ nav:
- 'Relations': mathematics/set-theory/relations.md
- 'Maps': mathematics/set-theory/maps.md
- 'Permutations': mathematics/set-theory/permutations.md
- 'Orders': mathematics/set-theory/orders.md
- 'Recursion and induction': mathematics/set-theory/recusrion-induction.md
- 'Cardinalities': mathematics/set-theory/cardinalities.md
- 'Additional axioms': mathematics/set-theory/additional-axioms.md
- 'Calculus':
- 'Limits': mathematics/calculus/limits.md
- 'Continuity': mathematics/calculus/continuity.md

View file

@ -0,0 +1 @@
# Additional axioms

View file

@ -0,0 +1 @@
# Cardinalities

View file

@ -0,0 +1,63 @@
# Recursion and induction
## Recursion
A recursively defined function $f$ needs two ingredients:
* a *base*, where the function value $f(n)$ is defined, for some value of $n$.
* a *recursion*, in which the computation of the function in $n$ is explained with the help of the previous values smaller than $n$.
For example, the sum
$$
\begin{align*}&\sum_{i=1}^1 i = 1,\\ &\sum_{i=1}^{n+1} i = (n + 1) + \sum_{i=1}^{n} i.\end{align*}
$$
Or the product
$$
\begin{align*}&\prod_{i=0}^0 i = 1,\\ &\prod_{i=0}^{n+1} i = (n+1) \cdot \prod_{i=0}^{n} i.\end{align*}
$$
## Induction
> *Principle* **- Natural induction**: suppose $P(n)$ is a predicate for $n \in \mathbb{Z}$, let $b \in \mathbb{Z}$. If the following holds
>
> * $P(b)$ is true,
> * for all $k \in \mathbb{Z}$, $k \geq b$ we have that $P(k)$ implies $P(k+1)$.
>
> Then $P(n)$ is true for all $n \geq b$.
For example, we claim that $\forall n \in \mathbb{N}$ we have
$$
\sum_{i=1}^n i = \frac{n}{2} (n+1).
$$
We first check the claim for $n=1$:
$$
\sum_{i=1}^1 i = \frac{1}{2} (1+1) = 1.
$$
Now suppose that for some $k \in \mathbb{N}$
$$
\sum_{i=1}^k i = \frac{k}{2} (k+1).
$$
Then by assumption
$$
\begin{align*}
\sum_{i=1}^{k+1} i &= \sum_{i=1}^k i + (k+1), \\
&= \frac{k}{2}(k+1) + (k+1), \\
&= \frac{k+1}{2}(k+2).
\end{align*}
$$
Hence if the claim holds for some $k \in \mathbb{N}$ then it also holds for $k+1$. The principle of natural induction implies now that $\forall n \in \mathbb{N}$ we have
$$
\sum_{i=1}^n i = \frac{n}{2}(n+1).
$$